2015
DOI: 10.3109/23337931.2015.1068126
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sintering temperature and duration on the flexural strength and grain size of zirconia

Abstract: Objective: This study investigated the effect of different sintering temperatures and times on the flexural strength and grain size of zirconia. Material and methods: Zirconia specimens (In-Coris ZI, In-Coris TZI, 120 samples) were prepared in a partially sintered state. Subsequently, the specimens were randomly divided into three groups and sintered at different final sintering temperatures and for various durations: 1510 °C for 120 min, 1540 °C for 25 min and 1580 °C for 10 min. Three-point flexural strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 33 publications
(25 reference statements)
6
66
1
2
Order By: Relevance
“…After reading and analyzing the full texts of the 11 studies, the following factors were studied in terms of their effects on the alteration of sintering of monolithic zirconia: Microstructure (grain size) Mechanical properties Optical properties …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading and analyzing the full texts of the 11 studies, the following factors were studied in terms of their effects on the alteration of sintering of monolithic zirconia: Microstructure (grain size) Mechanical properties Optical properties …”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that the grain size of 3Y‐TZP zirconia increased as the sintering temperature was increased above 1300°C, with the greatest grain size occurring at 1700°C, and the that sintering temperature showed a significant negative correlation with flexural strength and the contrast ratio ( P < .001) . In contrast, another study showed that a combination of a high sintering temperature with a short sintering time increased the flexural strength of zirconia, but no further analysis of the results was provided. Therefore, the results so far are inconclusive in regard to the relationship between increased sintering temperature and flexural strength.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct superscript letters within the same row indicate statistical differences among groups. * The flexural strength data were published by Dr. Ersoy and colleagues in 2015 [16]. Data were obtained using the 3-point bend test with bar specimens of 1.2 × 4 × 25 mm in dimension ( n = 20) according to ISO 6872.…”
Section: Figmentioning
confidence: 99%
“…Novel speed and super-speed sintering protocols have been developed [16] to meet the demand for time and cost effective chairside one-visit CAD/CAM-produced restorations, as well as to prevent Y-TZP grain growth for better translucency. The effect of speed sintering on the flexural strength of monolithic Y-TZP has been investigated [16], showing that no significant difference was observed in the flexural strength of Y-TZP when speed sintered with a dwell time of 25 min at 1540 °C ( σ =622.3 ± 82.7 MPa) and conventionally sintered with a dwell time of 120 min at 1510 °C ( σ =579.7± 130.6 MPa). However, when super-speed heating and cooling rates, as well as a short dwell time, were used (the sample was placed in a 1580 °C pre-heated furnace and removed after 10 min dwell time), the flexural strength achieved was much higher (904 ± 115.7 MPa).…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmada tercih edilen son sıcaklık değeri sinterleme iş-leminin gerçekleştirildiği fırında kullanılabilecek en kısa süreli programlardan biridir. Bu programın, farklı çalışma-larda zirkonyanın tanecik boyutu 28 , mekanik özellikleri ve farklı yüzey işlemleri sonrası seramik ile bağlantısı 29 üze-rine etkileri araştırılmış ve faz geçişlerinin tamamlandığı belirtilmiştir. Bu amaçla bu çalışmada ekstradan x-ışını difraksiyon (XRD) incelemesi yapılmamıştır.…”
Section: Discussionunclassified